Isolation and characterization of a novel glycosyl hydrolase family 74 (GH74) cellulase from the black goat rumen metagenomic library - Song, Yun-Hee; Lee, Kyung-Tai; Baek, Jin-Young; Kim, Min-Ju; Kwon, Mi-Ra; Kim, Young-Joo; Park, Mi-Rim; Ko, Haesu; Lee, Jin-Sung; Kim, Keun-Sung (Folia microbiologica, 2017)
This study aimed to isolate and characterize a novel cellulolytic enzyme from black goat rumen by using a culture-independent approach. A metagenomic fosmid library was constructed from black goat rumen contents and screened for a novel cellulase. The KG37 gene encoding a protein of 858 amino acid residues (92.7 kDa) was isolated. The deduced protein contained a glycosyl hydrolase family 74 (GH74) domain and showed 77% sequence identity to two endo-1,4-β-glucanases from Fibrobacter succinogenes. The novel GH74 cellulase gene was overexpressed in Escherichia coli, and its protein product was functionally characterized. The recombinant GH74 cellulase showed a broad substrate spectrum. The enzyme exhibited its optimum activity at pH 5.0 and temperature range of 20-50 °C. The enzyme was thermally stable at pH 5.0 and at a temperature of 20-40 °C. The novel GH74 cellulase can be practically exploited to convert lignocellulosic biomass to value-added products in various industrial applications in future.
Keywords: klonování DNA; zvířata; exprese genu; sekvenční homologie; bachor; Goats; Cellulase; Recombinant Proteins; genová knihovna; Animals; Substrate Specificity; Escherichia coli; Rumen; Gene Expression; Hydrogen-Ion Concentration; molekulová hmotnost; rekombinantní proteiny; teplota; Enzyme Stability; Metagenomics; Sequence Homology; metagenomika; Metagenome; metagenom; Molecular Weight; Gene Library; genetické testování; koncentrace vodíkových iontů; substrátová specifita; kozy; celulasa; Temperature; stabilita enzymů; Genetic Testing; Cloning, Molecular; Fibrobacter